2017
DOI: 10.1111/pre.12185
|View full text |Cite
|
Sign up to set email alerts
|

Chronological change and the potential of recovery on the photosynthetic efficiency of Pyropia yezoensis f. narawaensis (Bangiales) during the sporelings frozen storage treatment in the Japanese Nori cultivation

Abstract: The chronological change of photosynthetic efficiency in a frozen storage treatment of the Japanese Nori cultivation industry was examined in the cultivated red alga, Pyropia yezoensis f. narawaensis (Saga-#5 Strain, Bangiales) by using pulseamplitude fluorometry. During the desiccation process that was conducted after the nursery cultivation season in November, the maximum quantum yield (F v /F m ) of the gametophytic sporelings growing on the Nori-net decreased monotonically with decreasing absolute water co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…The chlorophyll content and TPC of seagrape in spring has higher physicochemical quality than in summer and winter. The results from this research corresponding to the seasonal effect on the chemical content compositions, physiology, and growth of algae or seaweed [30,62]. Furthermore, Moreira et al [63] and Gosch et al [64] reported PUFA on algae was higher in winter than summer and spring, which results in higher lipids to generate MDA [65].…”
Section: Effect Of Cultivation Season On Physicochemical Quality Of Seagrape Under Post-harvest Storagesupporting
confidence: 54%
See 1 more Smart Citation
“…The chlorophyll content and TPC of seagrape in spring has higher physicochemical quality than in summer and winter. The results from this research corresponding to the seasonal effect on the chemical content compositions, physiology, and growth of algae or seaweed [30,62]. Furthermore, Moreira et al [63] and Gosch et al [64] reported PUFA on algae was higher in winter than summer and spring, which results in higher lipids to generate MDA [65].…”
Section: Effect Of Cultivation Season On Physicochemical Quality Of Seagrape Under Post-harvest Storagesupporting
confidence: 54%
“…Under water-limited conditions, the algae cannot regulate their water content that leads to oxidative stress [29]. Corresponding to the result in Figure 2, the weight loss of the seagrape without seawater during storage in every season is increasing as the representative of water loss [7,30]. While the without-seawater storage loses water content, the within-seawater storage increases their weight up to 10% after nine days of storage (Figure 2).…”
Section: Effect Of Oxidative Stress On Water Content Of Seagrapementioning
confidence: 67%
“…2011, 2016, Watanabe et al. 2017, Terada et al. 2020) found that desiccation causes water loss from the thallus and can eventually lead to a decrease in the Fv/Fm ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the Fv/Fm ratio can be considered an indicative parameter that reflects the PSII efficiency status under stress (Maxwell and Johnson 2000, Adams and Demmig-Adams 2004, Pang and Shan 2008, Gao et al 2013. Some authors (Wang et al 2011, Watanabe et al 2017, Terada et al 2020 found that desiccation causes water loss from the thallus and can eventually lead to a decrease in the Fv/Fm ratio. Yu et al (2013) found that emersed thalli experienced a short-term desiccation effect followed by complete recovery.…”
mentioning
confidence: 99%
“…P. yezoensis leafy thalli inhabit the intertidal zone and are extremely tolerant to stress (Watanabe et al . , ). It was reported that even when they had lost more than 85% of their original weight, they could still survive and recover physiological activity after rehydration (Blouin et al .…”
Section: Introductionmentioning
confidence: 99%